Effects of omega-3 supplementation on endothelial function, vascular structure, and metabolic parameters in adolescents with type 1 diabetes mellitus: A randomized clinical trial - Khorshidi, Masoud; Sayyari, Aliakbar; Aryaeian, Naheed; Olang, Beheshteh; Alaei, Mohammadreza; Khalili, Mitra; Hosseini, Amirhossein; Salehi, Masoud (Frontiers in Nutrition, 2022)
Background Vascular dysfunction is a major complication of diabetes mellitus that leads to cardiovascular disease (CVD). This study aimed to examine the effects of omega-3 consumption on endothelial function, vascular structure, and metabolic parameters in adolescents with type 1 diabetes mellitus (T1DM). Methods In this randomized, double-blind, placebo-controlled clinical trial, 51 adolescents (10–18 years) with T1DM completed the study. Patients received 600 mg/day [containing 180 mg eicosapentaenoic acid (EPA) and 120 mg docosahexaenoic acid (DHA)] of omega-3 or placebo for 12 weeks. Flow-mediated dilation (FMD), carotid intima-media thickness (CIMT), high-sensitivity C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR), triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), total cholesterol, blood urea nitrogen (BUN), creatinine, fasting blood sugar (FBS), hemoglobin A1C (HbA1c), homeostatic model assessment for insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI), serum insulin (SI), urine albumin-creatinine ratio (uACR), blood pressure, and anthropometric indices were assessed at the baseline and after the intervention. Results Following supplementation, omega-3 significantly increased FMD (3.1 ± 4.2 vs. −0.6 ± 4%, p = 0.006) and decreased TG (−7.4 ± 10.7 vs. −0.1 ± 13.1 mg/dl, p = 0.022) in comparison with the placebo group. However, no significant difference was observed regarding CIMT (-0.005 ± 0.036 vs. 0.003 ± 0.021 mm, p = 0.33). Although hs-CRP was significantly decreased within the omega-3 group (p = 0.031); however, no significant change was observed compared to placebo group (p = 0.221). Omega-3 supplementation had no significant effect on other variables. Conclusion Given the elevation in FMD and reduction in TG, omega-3 supplementation can improve vascular function and may reduce the risk of cardiovascular disease in adolescents with T1DM patients.